No exterior do cubo branco: Os veículos publicitários de mídia exterior como suporte para as intervenções artísticas no espaço urbano - Lamounier Lucas Pereira Junior (2007)
This text deals with the art that use the vehicles advertising executives of exterior media as support for its exhibition. From the relation between the Advertising and the Art, argue questions related to the public art in opposition to the art displayed in the museums, and analyze it aura of these workmanships and the successive crashes the one that this aura is submitted. A temporary artistic intervention in the urban space and its relation with the subjects treated throughout is also presented.